Systematic Evaluation of Drug-Loaded Hydrogels for Application in Osteosarcoma Treatment - (:unkn) unknown (BENTHAM SCIENCE PUBL LTD, 2016)
This is a literature review of studies focusing on the preparation of hydrogels for use as oncological drug delivery systems in the treatment of osteosarcoma (OS). The databases of the US National Library of Medicine National Institutes of Health, Embase, OVID, and Cochrane Library, and the references of retrieved studies, were traced from 1843 to December 21, 2015, without language restrictions. The obtained data were evaluated by complementary statistical methods. Potentially relevant studies were found and included in the analysis. OS-specific chemotherapeutic agents can be successfully embedded within the hydrogels and these drug-loaded hydrogels can be applied locally, rather than systemically, without organ tissue toxicity. Further, OS-specific drug-loaded hydrogels significantly increased tumor inhibition and decreased osteolysis and lung metastases. Drug-loaded hydrogels could be useful in the treatment of OS, although their development remains at the experimental phase. Following evaluation of their application in surgery and the completion of drug release kinetics studies, drug-loaded hydrogels could be tested on living mammals in large samples with the aim of applying these in clinical settings. In the future, development of such drug delivery systems and application of targeted approaches against osteosarcoma and other malignancies may render surgery, radiotherapy and chemotherapy unnecessary.
Keywords: Controlled release; drug delivery systems; hydrogel; steosarcoma treatment; IN-VITRO; DELIVERY-SYSTEM; DOXORUBICIN; CELL; CYTOTOXICITY; IMPLANTS; CULTURE; GROWTH